Election and Democratic Deepening in Indonesia: The Case of the 2024 Election - Andhik Beni Saputra; Andri Rusta (Jurnal Studi Sosial dan Politik, 2024)
The 2024 election is a crucial phase for Indonesian democracy. This election would be a juncture for whether the election is just a procedural mechanism for a power transition or a milestone in strengthening Indonesian democracy. This is due to the trend of Indonesian democratic regression characterized by narrowing space for civil liberties and weakening of the civilian institutions that support the existence of democracy. In this research, we use the concept of electoral integrity from Norris, Frank, and Coma. Electoral integrity emphasizes the fulfillment of free and fair principles throughout the election stages, that is, pre-election, campaigning, voting, and election evaluation. Electoral integrity directly contributes to democratic consolidation, which refers to the acceptance of democratic norms by the public such as law enforcement, transparency, deliberation, and bureaucratic integrity. This study uses a qualitative method. The data collection uses library research where data from secondary sources becomes the basis for compiling a conceptual framework and research analysis. The results of our study show that there are still several crucial issues during the 2024 election process that hinders democratic consolidation in Indonesia. Some critical points regarding the 2024 election are electoral regulations, party verification, voter registration, and electoral violations. The negligence of electoral integrity during the entire process of elections has the consequence toward the quality of the 2024 elections as a mere procedural mechanism. Even though the 2024 election has taken place peacefully, it is still insufficient to drive Indonesian democracy more substantive ways.